Inoperância e fracasso na defesa dos direitos humanos : o conselho de defesa dos direitos da pessoa humana na ditadura civil-militar(1964-1985) - Silva, Leonardo Fetter da (2019)
The Council for the Defense of Human Rights created in March 1964 had as their main objective the defense and promotion of human rights in Brazil and was composed by nine members of the state government and civil entities. After four years, in 1968, the civic-military dictatorship created the Council in an official ceremony and kept it operating until 1985 with the exception of Ernesto’s Geisel (1974-1979) government. Therefore, this dissertation proposes to investigate the trajectory of the CDDPH during the civic-military dictatorship (1964-1985), highlighting the regulatory role and its objective given to the agency by the regime as well as its members practices. In this way, we intend to stress how the Council was used by the regime to legitimate itself nationally and internationally, considering that its creation and maintenance did not pose an effective advancement in the protection of Human Rights in Brazil. In addition, we analyze the relation and acting of the CDDPH members with the regime, especially of those that promoted within the agency an “institutionalized resistance” – Associação Brasileira de Imprensa, Ordem dos Advogados do Brasil and the Movimento Democrático Brasileiro – forwarding reports and opposing the constant interventions on the Council. In order to develop this research we utilized official documents and the following journals: Correio da Manhã (RJ), O Estado de S. Paulo (SP) and Folha de São Paulo (SP). Thus, this research is divided into three parts, which also constitutes the chapters’ structure. Firstly, the trajectory of the Council during the period of 1964 until 1985, its modifications and performance as an agency. Secondly, the advisors acting and relations with the CDDPH and the civic-military dictatorship, as well as their attitude regarding the organization. Thirdly, the reports received by the Council at the time, highlighting the most argued and investigated cases, questions, problems and topics.